Psychological Impacts of COVID-19 on In-patients in a COVID-19 Dedicated Hospital in Bangladesh (Journal of Current and Advance Medical Research, 2025)
Background: COVID-19 is a global pandemic, and the World Health Organization has urged Southeast Asian countries to implement effective measures. However, countries like Bangladesh, with a poorly structured healthcare system and high population density, are struggling to meet these challenges.Objective: This study was aimed to assess the psychological impact of COVID-19 on patients at a COVID-19- dedicated hospital.Methodology: This cross-sectional study was conducted on 322 patients admitted with COVID-19 at Mugda Medical College and Hospital, a dedicated COVID-19 facility in Dhaka, Bangladesh, from May to June 2020. The Patient Health Questionnaire-9 (PHQ-9) was used to assess depression, the Generalized Anxiety Disorder-7 (GAD-7) scale measured the severity of self-reported anxiety, and the Insomnia Severity Index (ISI) was employed to diagnose self-reported insomnia.Results: This study assessed the psychological profiles of 382 patients. According to the PHQ-9 scale, 39.1% of patients had moderate depression, with 60.9% having severe depression. Anxiety levels were measured on the GAD-7 scale at 13.7% for moderate anxiety and 86.3% for severe anxiety. Based on the Insomnia Severity Index, 18.9% of patients suffered mild insomnia, 69.6% moderate insomnia, and 11.5% severe insomnia.Conclusion: The study has revealed that a significant proportion of COVID-19 patients experienced mental health disturbances during their hospitalization. It is essential to closely monitor their mental well-being and provide timely interventions.Journal of Current and Advance Medical Research, January 2024;11(1):28-33